Growing up and away narratives of Indian childhoods memory, history, identity - Balakrishnan, Vijayalakshmi (New Delhi ; Oxford : Oxford University Press, 2011)
Tracing the evolution of child rights in India, this book gives an insight into the state-child relationship in the post-Independence era. It critically evaluates the initiatives taken for child development and for advancing the issue of child rights.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Children's rights -- India; Children's rights -- Government policy -- India; Child welfare -- India